The impacts of the minimum wage on post-secondary enrollment and retention - Alessandrini, Diana; Milla, Joniada (My University, 2024)
Previous studies have shown that the minimum wage can reduce enrollment at the secondary and post-secondary level. The effects of the minimum wage are more heterogeneous than previously thought and differ by type of post-secondary program. The minimum wage affects enrollment differently in university versus community college. In addition, these impacts vary by students’ demographics, socio-economic background, and employment history.
Keywords: Education, training & learning; Government